Network and stoichiometry analysis revealed a fast magnesium and calcium deficiency of mulched Phyllostachys violascens - Zhou, Hanchang; Huang, Siyuan; Zhang, Ziying; Li, Ting; Li, Yi; Zhuang, Guoqiang; Liu, Guohua; Fu, Bojie; Kuang, Xiaobao (Frontiers in Plant Science, 2024)
The imbalanced fertilization and the consequential deterioration on rhizosphere microbial community (RMC) were two potential reasons for the quick yielding degradation of Phyllostachys violascens (Lei-bamboo), a high-value shoot-oriented bamboo. However, most research only focused on the nitrogen, phosphorus and potassium, the studies on the dynamics of other nutrients, such as calcium and magnesium, and their driving mechanisms, lags far behind. Thus, Lei-bamboo fields of different mulching and recovery ages were selected to investigate the dynamics of calcium and magnesium in both soil and bamboo tissue, and to explore their relationship to RMC composition and network patterns. The results showed that mulching increased the content of soil acidification, total organic carbon, alkali-hydrolysable nitrogen, available phosphorus and available potassium, but reduced soil exchangeable magnesium and calcium in soil as well as the magnesium and calcium content in rhizome, stem and leaf of Lei-bamboo, which indicated an increased relative limitation on magnesium and calcium. Mulching also enhanced the α-diversity and reshaped the composition of RMC, which had a close link to Mg rather than nitrogen, phosphorus and potassium. As the mulching years increased, the RMC network became bigger and more complex, and the magnesium and calcium gradually appeared in the network center, which further support the magnesium and calcium deficiency to RMC. Nearly all the variation mentioned above could be revered after the removing of mulching. Structural equation modeling showed two main pathways that mulching leads to magnesium and calcium deficiency in Lei-bamboo, one is directly by lowering soil magnesium and calcium content, the other one is indirectly by improving RMC network interactions, a sign of weakened mutualism between RMC and plant roots that hampering the uptake of nutrients. This research highlights the quick magnesium and calcium deficiency caused by mulching in Lei-bamboo forest and the contribution of RMC in amplify the effects of soil magnesium and calcium deficiency, which offers valuable information on balancing fertilization pattern for future sustainable Lei-bamboo cultivation.